Penilaian Beban Kerja dan Potensi Cedera pada Pekerja Menggunakan Metode REBA (Rapid Entire Body Assesment) - Amri, Yusril; Riana, Iis; Hamidah, Nur (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
CV. Budidaya Jamur Sejati is a place for cultivating mushrooms such as oyster mushrooms. There are seven work stations, namely mixing work stations, pressing baglogs, ovens, lifting baglogs from the oven to Inoculation, nurseries, Harvesting and sorting. This study aims to determine the risk value of the operator’s work posture and propose and improve work stations that are very risky. The method applied in this study is the Rapid Entire Body Assessment (REBA) method based on the Nordic Questionnaire assessment. This method assesses the operator’s body position while working which has the potential to cause problems in the back, waist, hips, right hand and feet. The results of data collection and processing show that operators are at high risk of injury with the actual work system based on REBA, with the highest risk at the accessory installation work station with a REBA score of 10 in the first activity, 4 in the 2nd activity and 11 in the 3rd activity. Solutions to prevent the risk of musculoskeletal disorders in workers need immediate improvements such as the use of back support, because many worker activities involve the spine as the axis of the body.